2018
DOI: 10.1108/imefm-03-2017-0066
|View full text |Cite
|
Sign up to set email alerts
|

What drives consumer choice of Islamic banking services in the United Arab Emirates?

Abstract: Purpose Islamic banking (IB) has witnessed remarkable growth in the past decade. The purpose of this study is to explore some factors that are influencing the choice of Islamic banking and finance (IBF) products and services in the United Arab Emirates (UAE), a predominantly Muslim country. Design/methodology/approach Students enrolled at a university located in a major emirate in the UAE were asked to respond to a survey on factors underlying their decision to open an account at an Islamic bank. Responses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 49 publications
4
56
1
Order By: Relevance
“…The results of this study are in accordance with the results of previous studies. Shome, Jabeen, & Rajaguru (2018) failed to prove the significant effect of education and gender on consumers' decision to choose the services of Islamic banks at the United Arab Emirates. Kaakeh et al (2018) also showed that the potential of Islamic banking customers in Spain are Muslim (Spanish, Moroccan or Pakistani), male, and did not reach university degrees in their education.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in accordance with the results of previous studies. Shome, Jabeen, & Rajaguru (2018) failed to prove the significant effect of education and gender on consumers' decision to choose the services of Islamic banks at the United Arab Emirates. Kaakeh et al (2018) also showed that the potential of Islamic banking customers in Spain are Muslim (Spanish, Moroccan or Pakistani), male, and did not reach university degrees in their education.…”
Section: Discussionmentioning
confidence: 99%
“…The United Arab Emirates:Shome et al (2018), targeting university students, find that students' Arabic language skills and their expectations in terms of the conformity of a bank's operations with Islamic principles are the main factors that affect their decision to open an account with an Islamic bank. On the other hand, factors such as students' nationality, gender, education and familiarity with Islamic banking are not seen to have any effect on the decision to open an account with an Islamic bank.…”
mentioning
confidence: 99%
“…In term of the sharia compliance in financial transaction, Usman et al [37] found that not all Muslim obey the tenets, and only those who perceived bank interest as usury strictly choose Islamic banks while conducting their transactions. However, most studies confirm that religiosity become one of the considerations of customers when they choose Islamic bank [2], [7], [8], [39]. Hence, we proposed following hypotheses:…”
Section: Religiosity Dimensionsmentioning
confidence: 98%